Emotional Question of Students in Undergraduate Course of School of Nursing Hasanuddin University - Desy Ana Hendra; Hapsah Hapsah; Silvia Malasari; Yuliana Syam; Andriani Andriani (Indonesian Contemporary Nursing Journal, 2017)
Introduction: Lower level of caring in Indonesian nurses related to emotional intelligence level of nursing, and  assertion to nurses for always being professional in any circumstances and this condition relatated to emotional intelligence which is formed when undergoing nursing education along emotional intelligence phenomena  in nurses period of education and period of profession education  between regular students and non-regular students. Method: the design of this study is descriptive research with crossectional approach. Sample selection technique using disproportionate stratified random sampling, with the number of respondent about 128 respondents. Primary data was obtained through a TEIQUE questionnaire in the form of question about Emotional Itelligence and the ability of recognizing emotion, managing emotion, self motivation, empathy, social skill Result: This study shows that, 55 % respondents have a high emotional intelligence and higer in term of recognizing emotion ability (80.5 %), managing emotion ability (56.3 %), self motivation ability (92.2 %), empathy ability (59.4 %), and social skill ability (63.3 %). Respondent characteristics who have higer in emotional intelligence were from adults (56.4 %), woman (56.4 %), unreguler students (96.4 %), widow/widowed marriage status (69.2 %), student who do not entered any organization (76.1 %), and students in seventh grade (69.4 %).Conclusion: : the result showed that more than half respondents have higer emotional intelligence (managing emotion ability, self motivation ability, empathy ability, social skill ability ) so that give us information about description of Emotional Intelligence in Undergraduate Hasanuddin University Nursing Students.